The Effect Of The Combination Of PMR (Progressive Muscle Relaxation) With Music On Ankle Brachial Index On Type II Diabetes Mellitus Patients - Farida, Denis; Yuliastuti, Retno Ayu (STRADA : Jurnal Ilmiah Kesehatan, 2020)
Quasi-experimental research design with a pre-post-test control group design approach. The sample size was 32 respondents divided into 16 intervention groups and 16 control groups. The intervention group was given a combination of PMR with music for 1 month. The control group was not given an action. The instrument uses an observation sheet. The study used a paired t-test and independent t-test with α <0.05. The results showed the mean value. intervention group before exercise 0.74 and after exercise 0.90 mg / dl. The control group before treatment has obtained an average. 0.77 and after treatment an average ABI was 0.75. Based on the independent t-test, blood sugar levels were obtained ρ 0.000 (α <0.05). So that H0 is rejected, meaning that there is an effect of the combination of PMR and music on (ABI). The combination of PMR with music that is routinely performed can increase the ABI value